How outer space made America : geography, organization and the cosmic sublime - Sage, Daniel, 1980- (Ashgate, 2014)
In this innovatory book Daniel Sage analyses how and why American space exploration reproduced and transformed American cultural and political imaginations by appealing to, and to an extent organizing, the transcendence of spatial and temporal frontiers. While largely engaging with the historical development of space exploration, it shows how contemporary cultural and social, and indeed geographical, research themes, including national identity, critical geopolitics, gender, technocracy, trauma and memory, can be informed by the study of space exploration.